2023
DOI: 10.1152/ajplung.00105.2022
|View full text |Cite
|
Sign up to set email alerts
|

A proteomics approach to identify COPD-related changes in lung fibroblasts

Abstract: Background: Lung fibroblasts are implicated in abnormal tissue repair in chronic obstructive pulmonary disease (COPD). The exact mechanisms are unknown and comprehensive analysis comparing COPD- and control fibroblasts is lacking. Aim: To gain insight in the role of lung fibroblasts in COPD pathology using unbiased proteomic and transcriptomic analysis. Methods: Protein and RNA was isolated from cultured parenchymal lung fibroblasts of 17 stage IV COPD patients and 16 non-COPD controls. Proteins were analyzed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…Other studies investigating only the differences between baseline healthy and COPD lung fibroblasts which can lead to inadequate conclusions that pathways involved are associated with COPD and not healthy. 18 Whereas differences found here at baseline reflected that the healthy lung fibroblast responded far more than the COPD. Therefore, it is important to assume that differences in biomarkers at baseline would not reflect targetable markers for COPD therapeutics.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Other studies investigating only the differences between baseline healthy and COPD lung fibroblasts which can lead to inadequate conclusions that pathways involved are associated with COPD and not healthy. 18 Whereas differences found here at baseline reflected that the healthy lung fibroblast responded far more than the COPD. Therefore, it is important to assume that differences in biomarkers at baseline would not reflect targetable markers for COPD therapeutics.…”
Section: Discussionmentioning
confidence: 65%
“…Although several studies have compared large arrays/profiles of gene expression from cells of COPD subjects to control subjects, [13][14][15][16][17][18] no studies were found in regard to the effects of CSE stimulation. A broad and quantitative assessment of lung fibroblast expression should elucidate more accurate mechanisms that differentiate healthy and COPD responses to CSE giving insight into more targetable pathways for treatments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation